Analisis Kesalahan Siswa Kelas IV SDN Serang 8 dalam Menyelesaikan Soal Cerita pada Materi Pengukuran - Damayanti, Intan Shella; Tiurlina, Tiurlina; Fitriasari, Novi Sofia (Didaktika, 2021)
This research described the students' errors in solving story qustions in grade IV SDN Serang 8. Most students find it difficult to interpret the purpose of the calculation questions in the form of stories and often get less scores because of the errors students make when students answer calculation questions in story form. This study aimed to find out what are the causes and errors made by students, then find out how the solutions can be given and carried out by students or teachers. This research used a qualitative approach with the descriptive type of research. By using content analysis methods, namely research by examining the text of documents or books to draw conclusions based on the context of their use. The data collection procedure was carried out by giving several research instruments in the form of 4 mathematical story questions about measurement and conducting interviews to produce oral data from participants. The findings of this study indicate that there are several facts that cause this occurrence of students’ errors. They are students did not understand the concept, students made calculation errors, some students did not answer correctly, and students did not answer in a complete way until the final answer. Researcher produced data on the level of ability of grade IV SDN 8 students. There are 3 students who have high ability level, 10 students have medium ability level, and 7 students have low ability level. This research was expected to help to provide solutions so that students are able to solve story problems correctly and according to the procedure for solving them.